A water dissolution method for removing micro-waviness caused by SPDT process on KDP crystals. Issue 5 (July 2016) - Wang, Xu; Gao, Hang; Chen, Yuchuan; Guo, Dongming
Abstract Single crystals of potassium dihydrogen phosphate (KDP) are an irreplaceable optical material in laser-induced inertial confinement fusion (ICF), where they are used as electro-optic switches and for laser-frequency conversion. The KDP lenses used in ICF applications must be pristine, high quality, and have a surface roughness of less than 3 nm. Currently, single-point diamond turning (SPDT) is the primary method for performing ultra-precision machining on KDP crystals. However, after the SPDT process, the crystal surface exhibits micro-waviness and subsurface damage, both of which have adverse effects on the optical performance of the KDP elements, especially the laser-induced damage threshold. In this study, a new method of micro-dissolution polishing was developed, which is based on the solubility of KDP crystals in water, to achieve controllable material removal. A material removal function was formulated to describe the material removal in terms of both the path and parameters used to polish the SPDT-machined samples with a small polishing tool. An experimental study showed that this method is able to reduce the surface micro-waviness and surface roughness (from 6.205 to 2.107 nm) significantly. The method is also applicable to the polishing of other water-soluble materials.